Peripheral odontogenic myxoma of maxillary gingiva: A rare clinical entity - Vijay Kumar Jain; Soundarya Narayana Reddy (Journal of Indian Society of Periodontology, 2013)
Odontogenic myxoma comprises 3-6% of all odontogenic tumors. Odontogenic myxomas are relatively rare benign mesenchymal tumors found exclusively in the tooth-bearing areas of the jaw and are usually located centrally in the mandible. Soft-tissue localization is rarely seen and is classified as peripheral myxoma. Peripheral myxoma is slow growing and less aggressive, as compared to the central myxoma. It has a low recurrence rate. Till date, only few cases of maxillary gingival myxomas are reported in the literature. Here, we present an unusual case of primary peripheral odontogenic myxoma occurring in the gingiva of anterior maxilla in a 41-year-old female patient.